The methods of calculation of pollution agents discharge into ambient air at hot processing of metals - V. V. Hodin; N. I. Milanovich (Литьë и металлургия, 2003)
On the basis of summarizing of statistics there is developed the methods of calculation of pollutants discharge into ambient air at heat processing of metals.